IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA DIGITAL UNTUK MENINGKATKAN HASIL BELAJAR DAN KEAKTIFAN PADA SISWA SMA NEGERI 13 MEDAN - Nurfatima Amalia; Rika Kartika; saipul (STKIP Subang, 2025)
This study aims to improve the learning outcomes and student engagement of tenth-grade students at SMA Negeri 13 Medan through the implementation of the Problem Based Learning (PBL) model assisted by digital media. This Classroom Action Research (CAR) was conducted in two cycles, each consisting of planning, action implementation, observation, evaluation, and reflection stages. The research subjects were 36 tenth-grade students, with variables focusing on student engagement and learning outcomes. Engagement data were collected using observation sheets filled out by the cooperating teacher, while learning outcomes were measured through evaluation tests. The results showed a significant increase in both student engagement and learning outcomes. The mastery percentage increased from 47.22% in the pre-cycle to 91.67% in the second cycle, and average student engagement rose from 83.77% in cycle I to 93.06% in cycle II. These findings indicate that the implementation of PBL assisted by digital media is effective in enhancing the quality of Indonesian language learning for tenth-grade students. This study recommends the use of this learning model as an alternative strategy that fosters an active, enjoyable, and meaningful learning environment.